“Enhancing Students’ Musical Competence through Multimedia and Interactive Technologies in Music Education” - Ochilov Zayniddin Saypiddinovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
ABSTRACT: This article explores the pedagogical effectiveness of multimedia and interactive technologies in music education and their role in developing students’ musical competence. Multimedia tools make lessons more interactive, engaging, and practically effective, enhancing students’ auditory skills, rhythm perception, and creative potential. The article also examines modern pedagogical approaches and digital platforms for integrating multimedia technologies into music education.